2014
DOI: 10.3171/2013.12.jns13184
|View full text |Cite
|
Sign up to set email alerts
|

An extent of resection threshold for recurrent glioblastoma and its risk for neurological morbidity

Abstract: For recurrent glioblastomas, an improvement in overall survival can be attained beyond an 80% EOR. This survival benefit must be balanced against the risk of neurological morbidity, which does increase with more aggressive cytoreduction, but only in the early postoperative period. Interestingly, this putative EOR threshold closely approximates that reported for newly diagnosed glioblastomas, suggesting that for a subset of patients, the survival benefit of microsurgical resection does not diminish despite biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(113 citation statements)
references
References 32 publications
5
98
0
1
Order By: Relevance
“…To supplement this method, we also performed formal tumor volumetrics using manual segmentation, as is commonly reported in glioma tumor series. 17,20 These data are most often described as "percentage of tumor resection" and "volume of residual tumor." Using a volumetric method to determine EOR provides information about the volume of residual tumor and is particularly useful if GTR was not the intention of surgery.…”
Section: Extent Of Tumor Resectionmentioning
confidence: 99%
“…To supplement this method, we also performed formal tumor volumetrics using manual segmentation, as is commonly reported in glioma tumor series. 17,20 These data are most often described as "percentage of tumor resection" and "volume of residual tumor." Using a volumetric method to determine EOR provides information about the volume of residual tumor and is particularly useful if GTR was not the intention of surgery.…”
Section: Extent Of Tumor Resectionmentioning
confidence: 99%
“…Although the consensus on the best treatment of recurrent disease is not as solid as with newly diagnosed disease, multiple retrospective studies support the excision of resectable recurrences. 17,19,28 However, with recurrent disease, issues of wound healing and the patient's functional status can hamper attempts of total resection. Moreover, recurrences often occur at sites close to functional or eloquent brain that were respected during the first surgery.…”
mentioning
confidence: 99%
“…Following a study with 170 patients, Oppenlander et al 23 concluded that an extent of resection larger than 80% in repeated surgery suffices to increase patients' survival.…”
Section: Extent Of Resection At Reoperationmentioning
confidence: 99%